Experimental and Analytical Study of High-Strength Concrete Containing Natural Zeolite and Additives - Iswarya Gowram; Beulah. M (Civil Engineering Journal, 2022)
The study compares the durability of Natural Zeolite with Metakaolin, Silica Fume, and Fly Ash on high-strength concrete. 300 concrete specimens were tested for compressive strength before and after an acid attack, modulus of elasticity, water absorption, and rapid chloride permeability. 5%, 10%, and 15% of the cement were replaced with cementitious elements while maintaining the same quantity of Natural Zeolite. In this investigation, the water-cement ratio was maintained at 0.35. After 28 days, the specimens were tested for durability. Samples of all mixes were TG/DT and FTIR tested. The optimal percentages of cementitious materials that resulted to the maximum durability enhancements were reported as the study results. Experimental results showed that Natural Zeolite and Metakaolin strengthened the durability of concrete. All the data show that 5% Natural Zeolite with 10% Metakaolin performs well. Good R2values and appropriate independent variable coefficients suggested that the regression findings for high-strength concrete durability were accurate. The P values of all models were less than 0.005 and the F values were statistically significant and appropriate; therefore, the generated models predict concrete's strength with authenticity. Doi: 10.28991/CEJ-2022-08-10-019 Full Text: PDF